Scheme Design of Linkage Between Staff Protection Key Switch in Fully Automatic Operation Signal System and Access Control System - LI Yong (Kongzhi Yu Xinxi Jishu)
On the rail transit lines designed for fully automatic operation (FAO), it is necessary to set up staff protection key switches (SPKS) in its signal system, to ensure the safety of personnel entering the automatic operation range. This paper first introduces the principles and methods of dividing protection areas respectively along the main line and at depots, and analyzes the SPKS-related operational process. In view of the safety loopholes that operators could enter the operation zone within the automatic operation range just by swiping the access control card given to them, it proposes a staff protection approach, which introduces a linkage function between SPKS and access control system (ACS) in the interlocking system, and presents designs for the interface circuit between SPKS and ACS, respectively under two types of interlocking systems: full-electronic interlocking and traditional computer-based interlocking. This approach aims to effectively avoid the potential safety risk that could arise due to operators straying into the unprotected zone of the automatic operation range.